A Bibliometric Analysis and Visual Review of Housing Policy Framework Development Research - Clinton Aigbavboa; Wellington Twala (The Thinker)
This study reviews housing policy f ramework development research published mainly in the Scopus database f rom 1994 – 2020 using a combination of bibliometric analysis and critical review. This study adopted a text mining tool, namely VOSviewer, to examine the bibliometric association in housing policy f ramework development research in a number of academic disciplines. Bibliometric analysis (publications per year, publications per country, co-author, co-citation, co-occurrence and their clusters) quantitatively visualized and critically reviewed housing policy research status quo and development.